Phosphorus extractability in relation to soil properties in different fields of fruit orchards under similar ecological conditions of Pakistan - Bibi, Sumera; Irshad, Muhammad; Ullah, Farid; Mahmood, Qaisar; Shahzad, Muhammad; Tariq, Muhammad Atiq Ur Rehman; Hussain, Zahid; Mohiuddin, Muhammad; An, Ping; Ng, A. W. M.; Abbasi, Asim; Hina, Aiman; et al. (Frontiers in Ecology and Evolution, 2023)
Productivity of an orchard generally depends upon the fertility of soil and requirements of nutrient for fruit trees. Phosphorus (P) availability from soils inﬂuences the P sorption, release patterns and P bioavailability. A study was carried out to ascertain the P extractability via seven extraction methods in relation to soil properties in three fruit orchards. Ten soil samples were collected from each fruit orchard namely citrus (Citrus sinensis L.), loquat (Eriobotrya japonica L.) and guava (Psidium guajava L.) located in Haripur district of Pakistan. Available P in the soil was extracted using deionized H2O, CaCl2, Mehlich 1, Bray 1, Olsen, HCl and DTPA methods. Selected soil properties (pH, EC, soil organic matter (SOM), texture, cation exchange capacity (CEC), macro- and micro-nutrients were also determined. Soils sampled from orchards indicated large differences in soil properties. Orchards trees have sequestered more amount of C stock than soil without an orchard. The extractability of P from soils and efficiency of extraction methods were profoundly affected in soils. The average amount of extractable P was relatively higher in those soils where the total amount of P was also higher. These methods extracted different pools of soil P with varying P concentrations regulated by soil properties. Phosphorus amounts extracted were varied in the order of HCl > DTPA > Mehlich 1 > Bray 1 > Olsen > CaCl2 > water. Among orchards, higher P level was found in soils of loquat followed by citrus and guava orchards. The extractable P was highly associated with the soil properties, like SOM, soil texture and CEC. Most of the extraction methods were positively correlated with each other. This study indicated that SOM inputs and turnover associated with orchard trees exhibited substantial extractable P in soils. Predicting available P in relation to its bioavailability using diversified methods in contrasting soils is required.